Oropharyngeal squamous cell carcinoma: p16/p53 immunohistochemistry as a strong predictor of HPV tumour status. Issue 3 (7th May 2021) - Benzerdjeb, Nazim; Tantot, Juliet; Blanchet, Christophe; Philouze, Pierre; Mekki, Yahia; Lopez, Jonathan; Devouassoux‐Shisheboran, Mojgan
Abstract : Aims: Oropharyngeal squamous cell carcinomas (OPSCC) related to human papillomavirus (HPV) infection have a better prognosis than those without HPV infection. Although p16 INK4a overexpression is used as a surrogate marker for HPV infection, 5–20% of p16‐positive OPSCC are described as being unrelated to HPV infection, with worse overall survival compared to OPSCC‐related HPV. There is therefore a risk of undertreating a proportion of OPSCC patients falsely considered to be HPV‐driven because of p16 positivity. TP53 mutations are highly prevalent in OPSCC driven by mutagens in tobacco and alcohol. We describe herein a combined p16/p53 algorithm to predict HPV tumour status in OPSCC. Methods and results: A total of 110 OPSCC were identified in the database of the pathology department and were studied using p16 and p53 immunohistochemistry. For p16‐positive or p16‐negative/wild‐type patterns‐p53 (WT‐p53) cases ( n  = 63), DNA in‐situ hybridisation for high‐risk HPV was performed, and if negative the HPV status was controlled by HPV DNA polymerase chain reaction (PCR) ( n  = 19). A significant association between TP53 mutation and pattern of p53 expression was found (WT‐p53, seven of 16, P  < 0.001). The p16‐positive/WT‐p53 was significantly associated with HPV + tumour status (p16‐positive/WT‐p53, 50 of 110, P  < 0.001). Interestingly, a subset of p16‐positive OPSCC was unrelated to HPV (13.5%, eight of 59), and showed mutant‐type staining of p53 expression. Conclusions: The p16 protein immunopositivity in conjunction with the mutant‐type pattern of p53 staining helped to reclassify a subset of p16‐positive OPSCC as OPSCC‐unrelated HPV. This approach could be routinely applied by pathologists involved in the management of OPSCC, because of their potential therapeutic implications. Abstract :